Sustainable Development in the Tasikmalaya Regional Apparatus Organization - Sundawa Bachtiar (Journal of Economics and Business (JECOMBI), 2022)
This study aims to find out how the sustainable development process is in the Tasikmalaya City regional apparatus organization, where in accordance with Law Number 23 of 2014 concerning regional government, that regional government has the authority to regulate and manage its own government affairs by referring to the principle of autonomy and co-administration then directed to accelerate the realization of community welfare through service improvement, empowerment, and community participation. The method used in this research is descriptive analysis, using a qualitative approach, and the results of this study explain that, as one of the regions in Indonesia that participates in the direction of local government policies, the City of Tasikmalaya has an obligation to plan development activities that refer to aspects sustainable development. At the regional government level, the City of Tasikmalaya, the sustainable development program will be aligned with the RPJMD (Regional Medium Term Development Plan) as a guideline and then a RAD (Regional Action Plan) for Sustainable Development Goals (TPB/SDGs) will be made which has been mandated in Presidential Regulation Number 59 of 2017, where the focus of this development will be more directed at consolidating the development of the industrial, trade and service sectors to be balanced with improving the quality of development in other sectors, such as the quality of infrastructure, human resources, health and the environment.